The potential of Indonesia waqf-venture in increasing welfare through islamic-socialpreneurship - ., Sulistyowati; Anshori, Muslich (Opción, 2019)
This paper aims to present the potential Indonesia Waqf Venture (IWV) in increasing social welfare through Islamic-social entrepreneurship. This study is exploratory research, using primary and secondary data by the documentary study of stakeholders of IWV. The findings are identified and summarized that Indonesia Waqf Venture has potentials in the several elements that are a demographic factor, productive and asset waqf, legal, and also human resources. In conclusion, Pentahelix of Indonesia Waqf-Venture (IWV) model is a finding by the author’s thought for an outstanding Waqf Venture.